Victims of Obtrusive Violence Children and Adolescents in Kenya - Lieten, G.K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume describes how children$1 (Bs experience with violence may affect and endanger their education, as well as their physical safety and their general well-being. It includes all forms of physical , psychological and sexual abuse, and neglect against children at home, at school, and in public spaces in two different areas of Kenya (rural and urban), while taking into account its environmental and cultural factors. This volume is unique, not only because of its focus on a less researched yet highly acute social problem but also because it provides inside knowledge by giving the children a voice through their direct participation in the data collection.s
Introduction -- Children in Kenya -- Peer-based research -- The impact of poverty -- Safety and Well-being of Children -- Violence against children at home -- Violence against children in the public space -- Violence against children in the public space -- (Non-) Support seeking -- Conclusions and recommendations.
Keywords: Social sciences; Educational sociology; Anthropology; Education and sociology; Sociology, Educational; Childhood; Adolescence; Social groups; Well-being.; Children; Social Sciences; Child Well-being.; Childhood, Adolescence and Society; Anthropology; Sociology of Education; Electronic books